Conduite de l’irrigation gravitaire par pilotage tensiométrique pour la conduite de Panicum virgatum(halophyte) - MOKEDDEM, Zohra (My University, 2016)
Irrigation is essential in semi arid climate. In addition to generating higher returns, it also allows the regular supply requested quality. Irrigation is very useful, but it requires in return an excellent governance: we must apply the right amount of water at the right time to avoid excess, unwanted water stress and loss of water and fertilizer in the environment. To ensure good governance of water, it is first necessary to know the needs of culture and the variation there of according to the stage of development. Also, it is imperative to regularly measure the soil water content. This information will clarify the moment conducive to irrigation and especially if the amounts applied are insufficient or excessive in relation to soil type and the need for culture. Knowledge of soil water status by tensiometric measures relates directly to improved irrigation and its management to provide farmers with their irrigation management methods (methods to judge the appropriateness of irrigate). This method is considered the most functional, simple is likely to be applied without major difficulties for the farmer. It can lead the irrigator to save water and reduce drainage and hence environmental risks. It is in this perspective that our course is inscribed, which took place in the laboratory soil analysis, I.N.S.I.D, El Matmar, Relizane. It allowed us to monitor the evolution of the water status of soil cultivated by tensiometric and gravimetric measurements. The specific objective of this work is to determine when, ie from any playback on the monitor, you have to start irrigation for that culture will not suffer water deficit and therefore we limit the drop in yield. Considering the results obtained at the study site, the water supply is renewed each time the voltage is observed between 60-80 centibars for trading 30 cm for our type of soil, so as not to limit the production potential of culture and risk of obstructing the smooth flow of water in the soil (can replenish by sprinkling on a sufficient depth of ground). It is noteworthy that 70 centibars, the useful is depleted to 50% for our type of soil. The present work shows the operational nature of the monitor to track the state of the water in the soil and can be used in open fields by farmers to control irrigation. However, it should be noted that the universal tensiometric provides guidance on the availability of water for plants, whatever the ground. For cons, the humidity measurements need to know the limits of the field capacity and the permanent wilting point.
Keywords: Pressure; water content of the soil; water stress; control; irrigation; Tensiomètre; tension; teneur en eau du sol; pilotage; stress hydrique